2013
DOI: 10.1016/s0034-7094(13)70221-6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hazards and Diseases Related to the Practice of Anesthesiology

Abstract: Control of occupational hazards to which anesthesiologists are exposed daily is necessary in order to develop an appropriate workplace and minimize risks to the good practice of anesthesiology. This contributes to decrease absenteeism, improve patients' care and quality of life of anesthesiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Awkward postures are a cause of work‐related musculoskeletal disorders . Although several publications mention potential risks for anaesthetists , there has been little research on the best posture when intubating . Previous studies have measured the distance from the head of the intubator to the head of a patient manikin whilst obtaining a view of the larynx .…”
Section: Introductionmentioning
confidence: 99%
“…Awkward postures are a cause of work‐related musculoskeletal disorders . Although several publications mention potential risks for anaesthetists , there has been little research on the best posture when intubating . Previous studies have measured the distance from the head of the intubator to the head of a patient manikin whilst obtaining a view of the larynx .…”
Section: Introductionmentioning
confidence: 99%
“…There are few publications about occupational health for anesthesiologists and the majority is related with sanitary regulations and recommendations by administrative agencies [14, 15]. Measuring previous knowledge is an important tool for further educational activities and our research found a considerable heterogeneity in the knowledge of occupational hazards and their prevention.…”
Section: Discussionmentioning
confidence: 86%
“…14,15 When both types of anaesthetics are used in combination, the limit for halogenated agents is reduced to 0.5 ppm. 16 The maximum concentration recommended by the NIOSH is several times lower than the least concentration recognised by the human olfactory systemfew people are able to perceive concentration of 33 ppm.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%